Validity of four commercially available metabolic carts for assessing resting metabolic rate and respiratory exchange ratio in non-ventilated humans. Issue 3 (March 2022) - Alcantara, J.M.A.; Galgani, J.E.; Jurado-Fasoli, L.; Dote-Montero, M.; Merchan-Ramirez, E.; Ravussin, E.; Ruiz, J.R.; Sanchez-Delgado, G.
Summary: Background & aims: The validity of most commercially available metabolic cart is mostly unknown. Thus, we aimed to determine the accuracy, precision, within-subject reproducibility, and concordance of RMR and RER measured by four commercially available metabolic carts [Cosmed Q-NRG, Vyaire Vyntus CPX, Maastricht Instruments Omnical, and Medgraphics Ultima CardiO2 ]. Further, we studied whether a previously proposed simulation-based post-calorimetric calibration of cart readouts [individual calibration control evaluation (ICcE)] modify the RMR and RER reproducibility and concordance. Methods: Three experiments simulating different RMR and RER by controlled pure gas (N2 and CO2 ) infusions were conducted on 5 non-consecutive days. Moreover, 30-min methanol burns were performed on 3 non-consecutive days. Lastly, the RMR and RER of 29 young non-ventilated adults (11 women; 25 ± 4 years-old; BMI: 24.1 ± 3.2 kg/m 2 ) were assessed twice using each instrument, 24 hours apart, under standardized conditions. Results: The Omnical presented the lowest measurement error for RER (Omnical = 1.7 ± 0.9%; Vyntus = 4.5 ± 2.0%; Q-NRG = 6.6 ± 1.9%; Ultima = 6.8 ± 6.5%) and EE (Omnical = 1.5 ± 0.5%; Q-NRG = 2.5 ± 1.3%; Ultima = 10.7 ± 11.0%; Vyntus = 13.8 ± 5.0%) in all in vitro experiments (controlled pure gas infusions and methanol burns). In humans, the 4 metabolic carts provided discordant RMR and RER estimations (all P < 0.001). No differences were detected in RMR within-subject reproducibility (P = 0.058; Q-NRG inter-day coefficient of variance = 3.6 ± 2.5%; Omnical = 4.8 ± 3.5%; Vyntus = 5.0 ± 5.6%; Ultima = 5.7 ± 4.6%), although the Ultima CardiO2 provided larger RER inter-day differences (4.6 ± 3.5%) than the others carts (P = 0.001; Omnical = 1.9 ± 1.7%; Vyntus = 2.1 ± 1.3%; Q-NRG = 2.4 ± 2.1%). The ICcE procedure did not modify the RMR or RER concordance and did not reduce the inter-day differences in any of the carts. Conclusions: The 4 metabolic carts provided discordant measurements of RMR and RER. Overall, the Omnical provides more accurate and precise estimations of RMR and RER than the Q-NRG, Vyntus and Ultima CardiO2, and might be considered the best for assessing RMR and RER in non-ventilated humans. Finally, our results do not support the use of an ICcE procedure.